Persistence of antibiotic resistance plasmids in bacterial biofilms. (8th May 2017) - Ridenhour, Benjamin J.; Metzger, Genevieve A.; France, Michael; Gliniewicz, Karol; Millstein, Jack; Forney, Larry J.; Top, Eva M.
Abstract: The emergence and spread of antibiotic resistance is a crisis in health care today. Antibiotic resistance is often horizontally transferred to susceptible bacteria by means of multidrug resistance plasmids that may or may not persist in the absence of antibiotics. Because bacterial pathogens often grow as biofilms, there is a need to better understand the evolution of plasmid persistence in these environments. Here we compared the evolution of plasmid persistence in the pathogen Acinetobacter baumannii when grown under antibiotic selection in biofilms versus well‐mixed liquid cultures. After 4 weeks, clones in which the plasmid was more stably maintained in the absence of antibiotic selection were present in both populations. On average plasmid persistence increased more in liquid batch cultures, but variation in the degree of persistence was greater among biofilm‐derived clones. The results of this study show for the first time that the persistence of MDR plasmids improves in biofilms.